Association Between 21-Gene Assay Recurrence Score and Locoregional Recurrence Rates in Patients With Node-Positive Breast Cancer - Woodward, Wendy A. (JAMA Oncol, 2020)
IMPORTANCE: The 21-gene assay recurrence score is increasingly used to personalize treatment recommendations for systemic therapy in postmenopausal women with estrogen receptor (ER)– or progesterone receptor (PR)–positive, node-positive breast cancer; however, the relevance of the 21-gene assay to radiotherapy decisions remains uncertain. OBJECTIVE: To examine the association between recurrence score and locoregional recurrence (LRR) in a postmenopausal patient population treated with adjuvant chemotherapy followed by tamoxifen or tamoxifen alone. DESIGN, SETTING, AND PARTICIPANTS: This cohort study was a retrospective analysis of the Southwest Oncology Group S8814, a phase 3 randomized clinical trial of postmenopausal women with ER/PR-positive, node-positive breast cancer treated with tamoxifen alone, chemotherapy followed by tamoxifen, or concurrent tamoxifen and chemotherapy. Patients at North American clinical centers were enrolled from June 1989 to July 1995. Medical records from patients with recurrence score information were reviewed for LRR and radiotherapy use. Primary analysis included 316 patients and excluded 37 who received both mastectomy and radiotherapy, 9 who received breast-conserving surgery without documented radiotherapy, and 5 with unknown surgical type. All analyses were performed from January 22, 2016, to August 9, 2019. MAIN OUTCOMES AND MEASURES: The LRR was defined as a recurrence in the breast; chest wall; or axillary, infraclavicular, supraclavicular, or internal mammary lymph nodes. Time to LRR was tested with log-rank tests and Cox proportional hazards regression for multivariate models. RESULTS: The final cohort of this study comprised 316 women with a mean (range) age of 60.4 (44-81) years. Median (interquartile range) follow-up for those without LRR was 8.7 (7.0-10.2) years. Seven LRR events (5.8%) among 121 patients with low recurrence score and 27 LRR events (13.8%) among 195 patients with intermediate or high recurrence score occurred. The estimated 10-year cumulative incidence rates were 9.7% for those with a low recurrence score and 16.5% for the group with intermediate or high recurrence score (P = .02). Among patients who had a mastectomy without radiotherapy (n = 252), the differences in the 10-year actuarial LRR rates remained significant: 7.7 % for the low recurrence score group vs 16.8% for the intermediate or high recurrence score group (P = .03). A multivariable model controlling for randomized treatment, number of positive nodes, and surgical type showed that a higher recurrence score was prognostic for LRR (hazard ratio [HR], 2.36; 95% CI, 1.02-5.45; P = .04). In a subset analysis of patients with a mastectomy and 1 to 3 involved nodes who did not receive radiation therapy, the group with a low recurrence score had a 1.5% rate of LRR, whereas the group with an intermediate or high recurrence score had a 11.1% LRR (P = .051). CONCLUSIONS AND RELEVANCE: This study found that higher recurrence scores were associated with increased LRR after adjustment for treatment, type of surgical procedure, and number of positive nodes. This finding suggests that the recurrence score may be used, along with accepted clinical variables, to assess the risk of LRR during radiotherapy decision-making.